Standard echocardiography versus handheld echocardiography for the detection of subclinical rheumatic heart disease: A systematic review - Telford, Lisa Helen (Department of Medicine, 2019)
Rheumatic heart disease (RHD) is a permanent heart valve condition resulting from an abnormal immune reaction to group A streptococcal (GAS) infection typically occurring in childhood. If left untreated, disease progression can result in irreversible heart valve damage, cardiac failure, stroke and premature death. Significantly, RHD is a preventable and treatable chronic condition which mostly effects disadvantaged populations across the world. Moreover, the continued persistence of RHD contributes to considerable amounts of preventable morbidity and mortality, predominantly among adolescents and young adults. The accurate detection of subclinical RHD in children and adolescents, however, remains hampered by the cost of diagnostic machinery and scarcity of trained personnel. Alternative RHD screening tests, which are both accurate and affordable, are therefore needed in many endemic areas. Recently, handheld echocardiography has become widely available with a variety of clinical uses. If shown to be sufficiently accurate, use of these handheld devices could potentially expand access to echocardiographic screening in RHD endemic areas. The research undertaken for this MPH dissertation compares the accuracy of handheld echocardiography for the detection of rheumatic heart disease to the reference standard using systematic review methods. The dissertation is structured into three parts.